Risk for physical dependence in community-dwelling older adults: The role of fear of falling, falls and fall-related injuries - Pereira, Catarina (2021)
Background: Falls and fall-related injuries along with fear of falling (FoF) seem to restrict activities of daily living (ADL), resulting in physical dependence. However, it is still unclear how falls and related injuries or FoF by themselves explain general and specific ADL dependence. Objectives: To investigate the relationships between falls and related injuries, FoF and physical dependence on ADL in community-dwelling older adults, controlling for age, gender, physical activity and physical fitness as confounders. Methods: This cross-sectional descriptive study assessed 588 community-dwelling older adults. Falls and fall-related injuries, ADL dependence on basic, instrumental and advanced activities, FoF, demographic characteristics and health conditions were assessed through a questionnaire. Physical activity was measured through the International Physical Activity Questionnaire. Physical fitness was assessed by the Senior Fitness Test and the Fullerton Advanced Balance Scale. Body composition was measured through bioimpedance. Results: Severe injuries occurrence increased the likelihood of moderate and high physical dependence by 3 and 6 times, while FoF increased this likelihood by 3 and 7 times, respectively. Also, the occurrence of previous falls, resulting in severe injuries, increased the likelihood of dependence in two instrumental ADL (3 and 4 times), while FoF increased this likelihood in numerous basic, instrumental and advanced ADL (2–3 times). The FoF was shown to explain overall physical functioning depend- ence, by itself, representing a constraint on the performance of most basic, instru- mental and advanced ADL. Conclusion: The FoF showed to be a greater threat to ADL dependence than falls and related injuries. Assessment guidelines for older adults living in the community should include the FoF in clinical evaluation. Implications for practice: Understand the isolated interplay of FoF and previous falls and injuries on ADL dependence among older adults allows healthcare professionals to perform more accurate clinical evaluations and develop more successful interven- tions to prevent further dependence.